2019
DOI: 10.1080/13575279.2019.1664988
|View full text |Cite
|
Sign up to set email alerts
|

The Barriers and Facilitators to the Implementation of Interventions for Children with Visual Impairments, Their Parents/Guardians or Educators: A Systematic Scoping Review

Abstract: A body of research indicates the importance of interventions for promoting the development and progress of children with visual impairments. However, the research available on suitable interventions for this population is relatively sparse. The purpose of this review is to identify, collate and appraise the available research evidence on implementation barriers and facilitators of interventions for children with visual impairments, their parents/guardians or educators. A systematic scoping search of peer-revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…A previous systematic review revealed several barriers to supporting children with VI in their home and school learning environments, including a lack of both teacher and parental training, a lack of knowledge about visual impairments, and a scarcity of research on children with VI and additional disabilities (Yeşilkaya et al, 2019). This review reported that collaborations between children, their parents/guardians, educators or health and support services and tailored practices contribute to planning successful strategies for meeting the individual needs of children with VI (Yeşilkaya et al, 2019). Thus, in view of the limitations identified in the literature, the present work aims to develop a logic model for parents/guardians, teachers, and children with VI who attend preschool or primary school by using the MRC framework for complex interventions.…”
Section: Identifying the Evidence Basementioning
confidence: 99%
See 2 more Smart Citations
“…A previous systematic review revealed several barriers to supporting children with VI in their home and school learning environments, including a lack of both teacher and parental training, a lack of knowledge about visual impairments, and a scarcity of research on children with VI and additional disabilities (Yeşilkaya et al, 2019). This review reported that collaborations between children, their parents/guardians, educators or health and support services and tailored practices contribute to planning successful strategies for meeting the individual needs of children with VI (Yeşilkaya et al, 2019). Thus, in view of the limitations identified in the literature, the present work aims to develop a logic model for parents/guardians, teachers, and children with VI who attend preschool or primary school by using the MRC framework for complex interventions.…”
Section: Identifying the Evidence Basementioning
confidence: 99%
“…However, some limitations exist regarding the development of comprehensive support strategies (Brambring et al, 1996; Chen, 2014) and these arise because there is no one‐size‐fits‐all comprehensive approach for this targeted population. A previous systematic review revealed several barriers to supporting children with VI in their home and school learning environments, including a lack of both teacher and parental training, a lack of knowledge about visual impairments, and a scarcity of research on children with VI and additional disabilities (Yeşilkaya et al, 2019). This review reported that collaborations between children, their parents/guardians, educators or health and support services and tailored practices contribute to planning successful strategies for meeting the individual needs of children with VI (Yeşilkaya et al, 2019).…”
Section: Identifying the Evidence Basementioning
confidence: 99%
See 1 more Smart Citation
“…This article, in the form of a scoping review, is an excellent example of why this link is critical to all practitioners, as it aims to "identify, collate and appraises the available research evidence on implementation barriers and facilitators of interventions for children with visual impairments, their parents/ guardians or educators" which can then lead not only to integrated working but also lead to positive changes in future practice (Yesilkaya et al, 2019, p.1).The second article by Flynn (2019) relates to the impact of austerity measures, arising from the Irish economic recession in 2008 and beyond, on intellectually disabled young people and their families. The intention, as with Yesilkaya et al (2019), is to lead to positive changes in future practice. Flynn (2019) uses a Framework Method of analysis applied to transcripts produced from a Biographical Narrative Interpretative Method (BNIM) of interviewing, across a…”
mentioning
confidence: 99%
“…The second article by Flynn (2019) relates to the impact of austerity measures, arising from the Irish economic recession in 2008 and beyond, on intellectually disabled young people and their families. The intention, as with Yesilkaya et al (2019), is to lead to positive changes in future practice. Flynn (2019) uses a Framework Method of analysis applied to transcripts produced from a Biographical Narrative Interpretative Method (BNIM) of interviewing, across a…”
mentioning
confidence: 99%